INDUSTRIALISASI DI INDONESIA: MENUJU KEMITRAAN YANG ISLAMI - M. Arif Hakim (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2009)
To accelerate the development process in a country, industrialization represents as an absolute and certain strategy, due to the paralelism between development and industrialization. Historical evidents records, as a developing country, Indonesia has made use of industrialization that results in shifting of economic activities, from agricultural sector to the industrial. On Islamic perspective, industrialization must be in accordance with maqahid syari'ah. Established partnership among corporates and small-scale industry must be in mutual benefit for all parties as it is indicated in the Quran